2020
DOI: 10.1101/2020.02.07.20021089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic overlap and causal associations between smoking behaviours and psychiatric traits and disorders in adolescents and adults

Abstract: Background: Epidemiological research shows that smoking is associated with psychiatric disorders and psychotic experiences, even after controlling for confounds such as cannabis use and sleep problems. We investigated degree of genetic overlap and tested for causal associations between smoking and psychiatric traits and disorders using genetic data. We tested whether genetic associations existed beyond genetic influences shared with confounding variables.Methods: Genetic correlations were estimated with LD-sco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Adams ( 2019 ), using a larger data set for the outcome than Sallis et al ( 2019 ), did not find clear evidence that neuroticism affects smoking. There was no clear evidence for causal effects of depression or bipolar disorder on smoking (Barkhuizen, Dudbridge, & Ronald, 2020 ; Vermeulen et al, 2019 ). Most studies also tested effects in the other direction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adams ( 2019 ), using a larger data set for the outcome than Sallis et al ( 2019 ), did not find clear evidence that neuroticism affects smoking. There was no clear evidence for causal effects of depression or bipolar disorder on smoking (Barkhuizen, Dudbridge, & Ronald, 2020 ; Vermeulen et al, 2019 ). Most studies also tested effects in the other direction.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed no clear evidence for causal effects (Bjorngaard et al, 2013 ; Skov-Ettrup, Nordestgaard, Petersen, & Tolstrup, 2017 ; Taylor et al, 2014a ; Wium-Andersen, Orsted, & Nordestgaard, 2015a ), with one exception: a small study ( n = 6294) of low-rated quality reporting that smoking decreased depression during pregnancy (Lewis et al, 2011 ). More recent studies, employing much larger samples, found strong evidence for causal, increasing effects of smoking initiation and lifetime smoking on depression and bipolar disorder risk (Barkhuizen et al, 2020 ; Vermeulen et al, 2019 ; Wootton et al, 2019 ). There was weak evidence that smoking initiation increases feelings of loneliness (a phenotype closely related to depression) from one study (Wootton et al, 2020 ), but no such evidence from another (Harrison et al, 2020b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation